Faktor-Faktor Dalam Literasi Keuangan Yang Berpengaruh Terhadap Keputusan Investasi Emas Pelaku UMKM Di PT Bank Syariah Indonesia Tbk - Syahrial, Syahrial; Raharja , Sapta; Pramudya, Bambang (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2022)
Financial literacy plays a very important role in encouraging the accessibility of financial products and services provided by formal financial institutions. Several studies on financial literacy state that financial education will affect the level of financial literacy and a person's behavior in managing their finances. An adequate level of financial literacy is one of the keys to getting access to capital and better welfare. MSME actors must have the adequate financial literacy to participate in the financial sector and have access to financial services such as saving, buying insurance premiums, investing, obtaining credit, and others. Therefore, in an increasingly advanced era, basic financial knowledge and adequate skills are needed to manage economic and financial resources effectively as well as reliable risk management to achieve better welfare. Inadequate financial literacy can result in low access to financial institutions and hinder the achievement of welfare. The aim of the research is to identify the factors in financial literacy, to analyze the factors in financial literacy that influence the investment decisions of MSME actors, and to recommend alternative strategies to increase MSME literacy. This study uses primary and secondary data derived from filling out questionnaires by respondents and the opinions of experts through interviews. Based on multiple linear regression analysis, the financial literacy factors, namely Age (X1) and Gender (X2), each partially have no effect on the decision-making of MSME gold investment in Indonesian Sharia Banks, while Education (X3), and Income (X4) each partially has a significant effect on the gold investment decision of MSME actors in Indonesian Sharia Banks. The results of the SWOT and AHP analysis showed that the priority strategy in increasing financial literacy is creating promotional media about the benefits of investing in gold for MSME actors.